The Mediating Effect of Emotion on Entrepreneurship Education and Business Opportunity Recognition - Nor Hafiza Othman; Norasmah Othman (International Journal of Business and Society, 2020)
The purpose of this study is to determine the effect of entrepreneurial emotion on relationship between entrepreneurship education and business opportunity recognition. Entrepreneurship process begins when an entrepreneur recognizes a business opportunity that involves various emotions throughout the process. Although various activities and entrepreneurship programs are carried out in universities, the involvements of students and graduates in business start-ups are still small. The main factor is the failure to leverage potential business opportunities, which in turn, leads to the stability of emotion’s reliance. A total of 152 of final year students participated in this study. The data were collected from questionnaires, and the hypotheses were tested using Partial Least Square - Structural Equation Modeling (PLS-SEM). The findings indicated that entrepreneurship education, emotion and opportunity recognition were significantly related. It was also found that entrepreneurial emotion partially mediated the relationship between entrepreneurship education and opportunity recognition. The findings have confirmed that although entrepreneurship education helps improve students’ capabilities to adapt to new environments, and recognizes the potential of business opportunities, a stable emotion is crucial throughout the entire entrepreneurship process.